Escape by deluge - Wignell, Edel. (Glebe, N.S.W. : Walter McVitty Books, 1989)
Mystery with blend of realism and fantasy - Australian.
Keywords: Literature and stories - Non indigenous - Fiction; Stories and motifs - Devils, monsters, evil spirits, hairy men, bunyips; Literature and stories - Juvenile; Environment - Climate and weather - Floods; Melbourne (Vic SJ55-05); Yarra River (Melbourne Vic SJ55-05, E Vic SJ55-06)